Effect of phosphate solubilizing analogue resistant mutants of Azotobacter chroococcum on sorghum - KUMAR, VIVEK; PUNIA, S S; LAKSHMINARAYAN, K; NARULA, NEERU (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during rainy season (kharif) 1995 on sorghum (Sorghum bicolor (L.) Moench) with phosphate sOlubilizing Azotobacter chroococcum to observe an interactive effect. Phosphate solubilising analogue resistant mutants ofAzotobacter chroococcum PS 2, PS 6 and PS 11 showed a positive interactive effect on ’HC 171’ sorghum. Different growth parameters like plant height, number of plants/m row length, green and dry fodder yield increased significantly by inoculation of different bacterial strains. Three levels of fertilizers were applied control (FLo)’ 90 kg N+ 11 kg P/ha (FLl) and 90 kg N + 26 kg P/ha (FL2). Without inoculation of sorghum seeds with bacteria and fertilizer level FL2 showed increased yield over control and FL1 with application of P solubilizing A. chroococcum strains there was no significnt difference on growth parameters at Fl1 and FL2 fertility levels indicating that inoculation of p_ solubilizing Azotobacter strains can reduce fertilizer levels from 26 kg P/ha to 13 kg P/ha. Â Â